Emotional intelligence characterization in university students at a nutrition bachelor’s degree - Torres-Zapata , Ángel Esteban; Lara-Gamboa , Carmen Cecilia; Pérez-Jaimes , Alejandra Karina; Estrada-Reyes , César Uziel; Brito Cruz, Teresa del Jesús (Horizonte Sanitario, 2022)
Objective: Identify the levels of emotional intelligence possessed by students of a Bachelor ofNutrition degree at a university in southeastern Mexico.Materials and methods: According to reviewed documental sources this is a quantitative study,with a descriptive non-experimental approach. In this research, a validated Salovery and MeyerTMMS-24, adapted to Spanish, was applied; this instrument consists of 24 items, subdivided intothree subscales or dimensions of the Likert type made up of five items. The sampling was nonprobabilistic,including 172 university students, who accepted the terms of the informed consent. Fordata analysis, the SPSS v.25 program was executed to assembly the information obtained throughdescriptive statistics (frequency, mean, median and percentage) and variability measures (range,standard deviation and variance). A t-Student test was performed for the analysis of means accordingto the levels, with a p value